2022
DOI: 10.1039/d1cy02143e
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic carbene iron complexes catalyze the ring-opening polymerization of lactide

Abstract: Poly(lactic acid), PLA, which holds great promises as a biodegradable substitute of fossil resource-derived polyolefins, is industrially produced by the ring-opening polymerization of lactide using a potentially harmful tin catalyst....

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 60 publications
(78 reference statements)
1
28
0
Order By: Relevance
“…To our knowledge, these figures represent the highest activities ever reported for lactide polymerization under industrially relevant conditions. 35 For comparison, we The molecular weights and the Đ values of the polymers were determined by SEC relative to polystyrene standards and multiplied by a correction factor of 0.58. b Calculated according to the monomer conversion: M n(calc) = [L-LA (equiv) ]/[BnOH (equiv) + X] × [144.13 g/mol] × [Conv.] (X is the number of monodentate alkoxide and alcohol groups bound to the metal).…”
Section: ■ Results and Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…To our knowledge, these figures represent the highest activities ever reported for lactide polymerization under industrially relevant conditions. 35 For comparison, we The molecular weights and the Đ values of the polymers were determined by SEC relative to polystyrene standards and multiplied by a correction factor of 0.58. b Calculated according to the monomer conversion: M n(calc) = [L-LA (equiv) ]/[BnOH (equiv) + X] × [144.13 g/mol] × [Conv.] (X is the number of monodentate alkoxide and alcohol groups bound to the metal).…”
Section: ■ Results and Discussionmentioning
confidence: 71%
“…Increasing the benzyl alcohol and l -lactide molar ratios to 1:107:107,000 (9.3 ppm of the catalyst) and extending the polymerization time to 100 min resulted in 92% conversion, and a further increase of molar ratios to 1:214:214,000 (4.7 ppm of the catalyst) resulted in 71% conversion after 120 min (Table , entries 1–3). To our knowledge, these figures represent the highest activities ever reported for lactide polymerization under industrially relevant conditions . For comparison, we attempted the polymerization of l -lactide employing the zirconium complex of the amine tris­(phenolate) ligand bearing tert -butyl phenolate substituentsLig t ‑Bu Zr­(O- i Pr) in a molar ratio of 1:55:55,000 (19 ppm catalyst) and found that after 30 min, the conversion was only 2% producing a low-molecular-weight oligomer as the product.…”
Section: Results and Discussionmentioning
confidence: 96%
“…Here we show that these complexes are indeed useful in this catalytic CO 2 fixation, and we provide support that the active species is the actual NHC iron species rather than dissociated NHC ligand, even though the NHC on its own is an excellent catalyst for CO 2 activation and the N -formylation of amines . The Fe–C NHC bond has been shown to be labile in the presence of moisture, even in chelated carbene complexes, though under dry conditions, it is persistent in the presence of silanes, alcohols, and amines, thus providing a useful starting point for amine formylation with CO 2 .…”
Section: Introductionmentioning
confidence: 63%
“…To evaluate the activity of piano-stool NHC iron complexes in CO 2 functionalization, a diverse set of complexes 1 – 7 was selected and prepared according to literature procedures (Figure ). ,,, These complexes contain different N -heterocyclic carbenes (imidazolylidene vs triazolylidene), various wingtip groups (aryl vs alkyl), and different spectator ligands (CO, iodide, NCMe, chelating pyridyl). Their catalytic activity was evaluated in CO 2 fixation via N -formylation of piperidine in the presence of PhSiH 3 .…”
Section: Resultsmentioning
confidence: 99%
“…N-heterocyclic carbene compounds with good electron donor ability have been used as monodentate ligands to synthesize their iron complexes 8−11 (Figure 3) and were investigated for the bulk ROP of rac-LA. 58 These catalysts exhibited excellent activities; especially catalyst 8 can efficiently polymerize rac-lactide at a high lactide:catalyst ratio with a TOF of 2100 h −1 (42% conversion for [rac-LA]:[Fe] ratio of 10000:1 at 150 °C in 2 h), producing a polymer with a molecular weight of 49 kg mol −1 , while high conversion of up to 91% could be achieved on decreasing the [rac-LA]:[Fe] ratio to 1000:1 and the resulting PLA had a moderate molecular weight of up to 5 × 10 4 g/mol with relatively narrow dispersity (Đ = 1.6). Under similar conditions, for a [rac-LA]:[Fe] molar ratio of 5000, the activity was decreased in the order 8 (2150 h −1 ) > 11 (1675 h −1 ) > 10 (1575 h −1 ) > 9 (1425 h −1 ).…”
Section: Iron Complexesmentioning
confidence: 99%